Oxidant-free oxidation of C–H bonds by cathodic hydrogen evolution: a phosphonic Kolbe oxidation/cyclization process. Issue 17 (31st July 2018) - Zhang, Lei; Zhang, Zhenxing; Zhang, Jianning; Li, Kangle; Mo, Fanyang
Abstract : An anodic oxidation/cyclization of 2-(aryl)aryl phosphonic acid monoesters for ethoxy dibenzooxaphosphorin oxide synthesis has been developed. Abstract : An anodic oxidation/cyclization of 2-(aryl)aryl phosphonic acid monoesters for ethoxy dibenzooxaphosphorin oxide synthesis has been developed. This unprecedented electrochemical oxidation reaction proceeds at room temperature with no oxidant or electrolyte required, and exhibits high atom-economy with H2 being the only byproduct. A series of ethoxy dibenzooxaphosphorin oxides were obtained in good yields.